Sleep toward heaven eaudiobook - Eyre Ward, Amanda (Recorded Books Inc., 2017)
Amanda Eyre Ward's debut novel is an intimate portrait of three women whose lives collide during a brutal Texas summer. In Gatestown, Texas, twenty-nine-year-old Karen Lowens awaits her execution with a host of convicted serial killers on death row. In Manhattan, Dr. Franny Wren, also twenty-nine, tends to a young cancer patient, and resists the urge to run from her fiancé and her carefully crafted life. In Austin, Texas, brassy Celia Mills, a once-vibrant librarian, mourns her murdered husband. Over the course of the summer, fate pushes these eerily recognizable women together, culminating in a revelation of the possibility of faith, the responsibility of friendship, and the value of life. Sleep Toward Heaven is a luminous story of murder and desire, solitude and grace—a rare literary page-turner where redemption seems perpetually within arm's reach.